Natalizumab exacerbates astrocytopathy in NMOSD via blockade of endothelial VCAM1–astrocytic integrin α4 interaction - Tingting Cui; Qing Wen; Zixuan An; Jingqi Kang; Pei Li; Yuechen Zeng; Lan Lin; Rui Gao; Guo Cheng; Luhang Dai; Zhe Feng; Ye Gong; et al. (Proceedings of the National Academy of Sciences, 2026)
Neuromyelitis optica spectrum disorder (NMOSD) is a rare autoimmune inflammatory disorder of the central nervous system (CNS) that shares clinical features with multiple sclerosis (MS) but typically manifests with more severe symptoms. The presence of pathogenic IgG autoantibodies targeting aquaporin-4 (AQP4) channels on astrocytes serves as a highly specific biomarker that distinguishes NMOSD from MS. Unlike MS, NMOSD is characterized by profound astrocytic destruction and exhibits a distinct response to therapies. Notably, disease-modifying therapies (DMTs) effective in MS, including natalizumab, interferon-β, and fingolimod, not only fail to benefit NMOSD patients but may also exacerbate disease progression. The precise molecular mechanisms underlying this immunomodulator-induced exacerbation, however, remain not yet fully elucidated. Here, we demonstrate that natalizumab alleviated experimental autoimmune encephalomyelitis (EAE) while exacerbating the autoimmune astrocytopathy in an “EAE-NMOSD” mouse model, a phenomenon associated with a reduction in actively proliferating astrocytes. Through molecular and signaling pathway analyses, we identify that endothelial-derived vascular cell adhesion molecule 1 (VCAM1) activates astrocytes via integrin α4 signaling, thereby mitigating astrocytopathy in NMOSD-like mice. Furthermore, astrocyte-specific integrin α4 deficiency exacerbates astrocytopathy, and notably, natalizumab-induced disease exacerbation does not occur in integrin α4-conditional knockout (CKO) mice. Finally, pharmacological activation of astrocytes rescues natalizumab-induced damage and ameliorates demyelination in NMOSD-like mice. Collectively, our findings provide mechanistic gaps regarding the clinical phenomenon underlying natalizumab-induced NMOSD exacerbation and suggest astrocyte-targeted therapeutic strategies as a potential intervention for NMOSD.